Environment-friendly mortar and preparation method thereof
By introducing porous composite structures and bioactive components into the mortar, the shortcomings of traditional mortar in terms of environmental protection and functionality are solved, high-performance and multifunctional mortar materials are realized, and modern building needs are met, and resource utilization efficiency is improved. Construction safety.
Patent Information
- Application Number
- CN202411607450.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-12
- Publication Date
- 2025-01-07
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Traditional mortars perform poorly when facing complex construction environments and high performance requirements, especially in terms of environmental protection and functionality, and cannot meet the energy-saving, environmental protection and comfort needs of modern buildings.
Using an environmentally friendly mortar, including components such as medium sand, silicate cement, fly ash, lime, gypsum, diatomaceous earth and seaweed extract, the porous composite structure and biological activity are formed through specific structural design and combination. Adhesives improve the insulation, adsorption and adhesion of the mortar, and improve its stability and uniformity through optimized processes.
It realizes efficient utilization of resources and reduced waste treatment, significantly improves the comprehensive performance of mortar, meets the demand for high-performance and multifunctional materials in modern buildings, and ensures the health and safety of the construction environment.
Smart Images

Figure CN119263742A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of mortar, and in particular to an environmentally friendly mortar and a preparation method thereof. Background Art
[0002] With the rapid development of the construction industry, mortar, as an indispensable material in construction, has a great influence on the stability and durability of buildings due to its performance and quality. Traditional mortar materials often focus on their basic physical properties, such as strength and adhesion, but have obvious deficiencies in environmental performance and functionality. Especially in the context of the increasing global environmental awareness, it is particularly important to develop a mortar material with both excellent physical properties and environmental characteristics.
[0003] The mortar materials in the prior art are usually simple in composition, mainly composed of sand, cement and a small amount of additives. Although this type of mortar can meet basic construction needs, it often seems to be unable to cope with the complex and changing construction environment and higher performance requirements. For example, traditional mortar performs poorly in terms of thermal insulation, sound insulation, moisture resistance and purification functions, and cannot meet the high requirements of modern buildings for energy conservation, environmental protection and comfort.
[0004] In addition, the existing mortar materials often ignore the design and optimization of the component microstructure during the preparation process. The microstructure of the components has a decisive influence on the macroscopic properties of the mortar. For example, the shape, size and distribution of sand particles, the structure and surface properties of cement particles, and the morphology and dispersibility of additives will directly affect the working performance, mechanical properties and durability of the mortar.
[0005] Therefore, we propose an environmentally friendly mortar and a preparation method thereof to solve the above problems. Summary of the invention
[0006] The purpose of the present invention is to solve the shortcomings of the prior art and to propose an environmentally friendly mortar and a preparation method thereof.
[0007] In order to achieve the above object, the present invention adopts the following technical solutions:
[0008] An environmentally friendly mortar comprises the following components in parts by weight: 450-510 parts of medium sand, 120-200 parts of Portland cement, 30-50 parts of fly ash, 20-25 parts of lime, 10-15 parts of gypsum, 5-15 parts of diatomaceous earth, 1-5 parts of seaweed extract, 4-7 parts of water-retaining thickener, 1-8 parts of retarder and early strength agent, and 1-5 parts of emulsifier.
[0009] As the preferred technical solution:
[0010] The environmentally friendly mortar as described above includes the following components in parts by weight: 480 parts of medium sand, 150 parts of silicate cement, 35 parts of fly ash, 22 parts of lime, 13 parts of gypsum, 8 parts of diatomaceous earth, 3 parts of seaweed extract, 5 parts of water-retaining thickener, 3 parts of retarder and early strength agent, and 2 parts of emulsifier.
[0011] The environmentally friendly mortar as described above, wherein the particle size of the medium sand is in the range of 0.3-0.45 mm, the quartz content in the mineral composition of the medium sand is not less than 90%, and the sum of feldspar and other impurity minerals does not exceed 10%; the clinker mineral composition in the silicate cement is: the content of tricalcium silicate is 50%-65%, the content of dicalcium silicate is 15%-30%, and the specific surface area of the silicate cement is 300-500m 2 / kg; the ignition loss of the fly ash is 1%-5%, the effective calcium oxide content in the lime is 85%-100%, the CaSO4·2H2O content in the gypsum is 95%-99%; the pore volume of the diatomaceous earth is 0.6-1.2cm 3 / g, pore size is 10-1000nm; the polysaccharide content in the seaweed extract is 60%-80%; the water-retaining thickener is one of wood fiber and cellulose ether, the retarder and early strength agent is one of sodium sulfate and calcium sucrose, and the emulsifier is OP-10.
[0012] In the environmentally friendly mortar as described above, the medium sand particles are distributed in the mortar in a linear arrangement, which is helpful to form an orderly skeleton structure; the silicate cement is modified; fly ash is compounded with other porous materials, including expanded perlite and ceramsite, to form a porous composite structure; in the lime, the lime particles have a hollow spherical structure and can form tiny bubbles in the mortar; in the gypsum, the gypsum particles have a mesoporous structure with a pore size of 2-50 nanometers.
[0013] As described above, in the environmentally friendly mortar, the medium sand particles are designed with a multi-layer structure, each layer has different physical and chemical properties, including hardness and water absorption, to enhance the layering and versatility of the mortar, and / or the medium sand particles are designed with a hollow structure, which can reduce the weight of the mortar while maintaining its strength and stability; in the silicate cement, the silicate cement particles adopt a core-shell structure, the core is high-strength cement clinker, and the outer shell has an auxiliary coating, the auxiliary coating includes waterproofing and corrosion resistance, and the silicate cement particles form a three-dimensional network structure in the mortar to increase the connection points and strength between the particles; in the fly ash, the fly ash particles are designed as a honeycomb structure; in the lime, the lime particles are designed as a nano-sheet structure; in the gypsum, the gypsum particles adopt a fibrous structure; in the diatomaceous earth, the diatomaceous earth particles have a nano-rod structure.
[0014] The second aspect of the present invention provides a method for preparing an environmentally friendly mortar, comprising the following steps:
[0015] S1: Mix medium sand, silicate cement and fly ash, stir them thoroughly in a dry state to ensure that the components are evenly distributed, add water and wet mix until the mixture presents a uniform mortar state to obtain a basic mortar;
[0016] S2: Mix lime and gypsum, add water to form a slurry, and then slowly add it to the base mortar while stirring to give full play to its gelling effect. Under the condition of continuous stirring, gradually add diatomaceous earth to improve the thermal insulation and adsorption of the mortar by using its porous structure;
[0017] S3: Spraying the seaweed extract in the form of an aqueous solution uniformly on the surface of the mortar obtained in S2, and then rapidly stirring it so that the seaweed extract can effectively penetrate into the mortar to enhance its adhesion and environmental protection. Subsequently, adding a water-retaining thickener to adjust the consistency of the mortar and improve its construction performance;
[0018] S4: Add retarder and early strength agent to adjust the setting time of mortar;
[0019] S5: Finally, add the emulsifier and stir at high speed to make the components in the mortar form a stable emulsified system, further improving the uniformity and stability of the mortar.
[0020] As the preferred technical solution:
[0021] In the method for preparing an environmentally friendly mortar as described above, in S1, a graded feeding technology is adopted, medium sand is first added, then silicate cement is added, and finally fly ash is added. After each feeding, a short dry mixing is performed to ensure that each component can be evenly distributed. Atomized water spraying technology is used to gradually add the required amount of water, and the stirring speed is increased at the same time to ensure that the water evenly penetrates into the mixture to form a mortar with a uniform texture, thereby obtaining a basic mortar.
[0022] In the method for preparing an environmentally friendly mortar as described above, in S3, a high-pressure spray device is used to evenly spray the seaweed extract aqueous solution on the surface of the mortar in the form of fine mist, and slow stirring is combined to ensure that the seaweed extract can penetrate deeply into the mortar. Subsequently, a water-retaining thickener is added to adjust the consistency of the mortar to improve its construction performance.
[0023] In the method for preparing an environmentally friendly mortar as described above, an emulsifier and water are pre-mixed into a uniform emulsion, which is then added to the mortar and stirred at high speed so that the components in the mortar form a stable emulsified system, thereby further improving the uniformity and stability of the mortar.
[0024] Compared with the prior art, the present invention has the following beneficial effects:
[0025] By introducing industrial waste fly ash as an important component of mortar, not only can the waste be recycled and the consumption of natural resources be effectively reduced, but the negative impact of waste on the environment can also be reduced, which is in line with the concept of sustainable development.
[0026] As an industrial waste, fly ash can replace part of cement and reduce resource consumption. Lime and gypsum can react with the active ingredients in fly ash. The combination of the three can not only realize their own functions, but also generate hydration products with cementitious properties, which can not only realize the resource utilization of waste, but also improve the strength and durability of mortar.
[0027] The introduction of seaweed extracts adds bioactive ingredients to the mortar, thereby improving its bonding and giving it better environmental performance. At the same time, the porous structure of diatomaceous earth significantly improves the thermal insulation and adsorption capacity of the mortar. The synergistic effect of these components enables the mortar to integrate a variety of beneficial functions while maintaining its basic properties, meeting the modern construction's demand for high-performance and multifunctional materials.
[0028] The raw materials used in this scheme are mostly from natural or industrial recycled materials, such as seaweed, diatomaceous earth and fly ash, which have little impact on the environment during production and use. At the same time, no toxic or hazardous substances are used in the preparation of mortar, ensuring the health and safety of the construction environment and use space.
[0029] In summary, through the synergistic effect of various components, this environmentally friendly mortar solution not only achieves efficient utilization of resources and reduced waste treatment, but also significantly improves the comprehensive performance of the mortar, providing the construction industry with a new type of building material solution that is both environmentally friendly and high-performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 This is a mortar specimen diagram of the present invention;
[0031] Figure 2 It is a data line chart of the embodiments and comparative examples of the present invention. DETAILED DESCRIPTION
[0032] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which the invention belongs. In the event of a conflict, the definitions in the specification shall prevail. "When mass, concentration, temperature, time, or other value or parameter is expressed as a range, a preferred range, or a range defined by a series of upper preferred values and lower preferred values, this should be understood to specifically disclose all ranges formed by any pairing of any upper range limit or preferred value with any lower range limit or preferred value, regardless of whether the range is disclosed separately. For example, a range of 1-50 should be understood to include 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41, 42, 43, 44, 45, 46, 47, 48, 49, 50, 51, 52, 53, 54, 55, 56, 57, 58, 59, 60, 61, 62, 63, 64, 65, 66, 67, 68, 69, 70, 71, 72, 73, 74, 75, 76, 77, 78, 79, 80, 81, 82, 83, 84, 85, 86, 87, 88, 89, 90, 91 6, 37, 38, 39, 40, 41, 42, 43, 44, 45, 46, 47, 48, 49, or 50, any number, combination of numbers, or subrange, and all decimal values between the above integers, for example, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, and 1.9. With respect to subranges, "nested subranges" extending from any endpoint within the range are specifically contemplated. For example, nested subranges of the exemplary range 1-50 may include 1-10, 1-20, 1-30, and 1-40 in one direction, or 50-40, 50-30, 50-20, and 50-10 in the other direction."
[0033] The present invention is further explained below in conjunction with specific examples. The experimental methods described in the following examples are conventional methods unless otherwise specified; the reagents and materials described are all commercially available unless otherwise specified.
[0034] An environmentally friendly mortar comprises the following components in parts by weight: 450-510 parts of medium sand, 120-200 parts of Portland cement, 30-50 parts of fly ash, 20-25 parts of lime, 10-15 parts of gypsum, 5-15 parts of diatomaceous earth, 1-5 parts of seaweed extract, 4-7 parts of water-retaining thickener, 1-8 parts of retarder and early strength agent, and 1-5 parts of emulsifier.
[0035] Among them, the particle size range of medium sand is 0.3-0.45mm, the quartz content in the mineral composition of medium sand is not less than 90%, and the sum of feldspar and other impurity minerals does not exceed 10%; the clinker mineral composition of silicate cement: tricalcium silicate content is 50%-65%, dicalcium silicate content is 15%-30%, and the specific surface area of silicate cement is 300-500m 2 / kg; the ignition loss of fly ash is 1%-5%, the effective calcium oxide content in lime is 85%-100%, the CaSO4·2H2O content in gypsum is 95%-99%; the pore volume of diatomaceous earth is 0.6-1.2cm 3 / g, pore size is 10-1000nm; the polysaccharide content in the seaweed extract is 60%-80%; the water-retaining thickener is one of wood fiber and cellulose ether, the retarder and early strength agent is one of sodium sulfate and calcium sucrose, and the emulsifier is OP-10.
[0036] Specifically, the medium sand particles are distributed in the mortar in a linear arrangement, which helps to form an ordered skeleton structure; the silicate cement is modified (nanomaterials or high molecular polymers are added); the fly ash is compounded with other porous materials, including expanded perlite and ceramsite, to form a porous composite structure to improve the thermal insulation and sound insulation properties of the mortar; in the lime, the lime particles have a hollow spherical structure, which can form tiny bubbles in the mortar, improving the construction performance and frost resistance of the mortar; in the gypsum, the gypsum particles have a mesoporous structure with a pore size of 2-50 nanometers, so as to increase its adsorption capacity for moisture and harmful substances and enhance the moisture-proof and purification functions of the mortar.
[0037] In the embodiment of the environmentally friendly mortar, in order to specifically realize the characteristics just described, the following steps can be followed:
[0038] Linear arrangement of medium sand
[0039] Choose medium sand with a particle size range of 0.355mm to 0.5mm to ensure that the sand particles can be arranged in a linear manner in the mortar. Through the mixing process, such as using a mixer with guide blades, ensure that the sand particles are arranged in an orderly manner in the mortar to form a stable skeleton structure.
[0040] Modification of Portland Cement
[0041] Ordinary Portland cement is selected as the base material. Nanomaterials, such as nano-silicon dioxide, are added at 1% of the cement mass to improve the strength and durability of the cement. Alternatively, high molecular polymers, such as polyvinyl alcohol (PVA), are selected at 0.5% of the cement mass to enhance the flexibility and crack resistance of the cement.
[0042] Composite of fly ash and porous materials
[0043] Use fly ash to replace 30% of the cement mass. Add expanded perlite and ceramsite in a composite manner, where expanded perlite accounts for 5% of the total volume of the mortar and ceramsite accounts for 3%. The introduction of these porous materials will form a porous composite structure in the mortar, effectively improving the thermal insulation and sound insulation performance.
[0044] Introduction of hollow spherical lime particles
[0045] Select lime particles with hollow spherical structure, with an average particle size of 0.1mm. Add such lime particles to the mortar at a ratio of 5% of the total mass of the mortar. The hollow spherical structure will form tiny bubbles in the mortar, improving construction performance and frost resistance.
[0046] Application of mesoporous gypsum particles
[0047] Gypsum particles with mesoporous structure are selected, and their pore size is mainly distributed in the range of 2-50 nanometers. Gypsum particles account for 10% of the total mass of the mortar. This mesoporous structure will increase the mortar's ability to adsorb moisture and harmful substances, thereby improving moisture-proof and purification functions.
[0048] Specifically, in medium sand, medium sand particles are designed with a multi-layer structure, each layer has different physical and chemical properties, including hardness and water absorption, to enhance the layering and versatility of the mortar, and / or design medium sand particles with a hollow structure, which can reduce the weight of the mortar while maintaining its strength and stability, which is conducive to achieving lightweight mortar; in silicate cement, silicate cement particles adopt a core-shell structure, the core is high-strength cement clinker, the outer shell is an auxiliary coating, the auxiliary coating includes waterproofing and corrosion resistance, silicate cement particles form a three-dimensional network structure in the mortar, increasing the connection points and strength between particles; in fly ash, powder The fly ash particles are designed with a honeycomb structure to provide more reaction surface area, promote its reaction efficiency with lime and gypsum components, and generate more beneficial hydration products; in lime, the lime particles are designed with a nanosheet structure, which can increase its contact area with the fly ash components, improve the reaction rate and gelling effect; in gypsum, the gypsum particles adopt a fibrous structure, which can increase its dispersibility and overlapping properties in the mortar, and improve the crack resistance and toughness of the mortar; in diatomaceous earth, the diatomaceous earth particles have a nanorod structure, which can increase its dispersion stability and long-range order in the mortar, and improve the mechanical properties and durability of the mortar.
[0049] In order to realize the special structural design of medium sand, silicate cement, fly ash, lime, gypsum and diatomaceous earth described, the following is a specific embodiment:
[0050] Example: Preparation of environmentally friendly mortar
[0051] 1. Multi-layer structure design of medium sand
[0052] Material selection: Choose natural medium sand as the base material with a particle size range of 0.35-0.5mm.
[0053] Multi-layer treatment: Through chemical deposition, multiple layers of coatings with increasing hardness and decreasing water absorption are formed on the surface of medium sand particles. For example, the first layer is a silicate coating with a thickness of about 5μm, and the second layer is an aluminum oxide coating with a thickness of about 3μm.
[0054] Data and effects: After multi-layer treatment, the hardness of the medium sand increased by about 20%, and the water absorption rate decreased to 60% of the original value, which significantly enhanced the layering and versatility of the mortar.
[0055] 2. Core-shell structure design of Portland cement
[0056] Material preparation: High-strength silicate cement clinker is used as the core, with an average particle size of 40 μm. Auxiliary coating preparation: A waterproof and corrosion-resistant auxiliary coating, such as a polymer-modified silicate coating, is formed on the surface of the cement clinker by the sol-gel method, with a thickness of about 10 μm.
[0057] Data and effects: The core-shell structure of silicate cement particles forms a stable three-dimensional network structure in the mortar, and the strength of the connection points is increased by about 30%, effectively enhancing the overall strength of the mortar.
[0058] 3. Honeycomb structure design of fly ash
[0059] Material processing: Through high temperature calcination and chemical activation treatment, a honeycomb structure is formed on the surface of fly ash particles, and the pore size is about 10-50μm.
[0060] Data and Effects: The honeycomb structure of fly ash provides more reaction surface area, and the reaction efficiency with lime and gypsum is increased by about 20%, generating more beneficial hydration products.
[0061] 4. Design of nanosheet structure of lime
[0062] Material processing: The lime particles are processed into a nano-sheet structure by mechanical grinding and chemical treatment, with a sheet thickness of about 50-100nm.
[0063] Data and effects: The contact area between the nano-sheet structured lime and fly ash is significantly increased, the reaction rate is increased by about 15%, and the gelling effect is significantly improved.
[0064] 5. Fibrous structure design of gypsum
[0065] Material selection: Natural gypsum ore is selected, crushed, ground, and then chemically treated to form a fibrous structure with a fiber diameter of about 1-5μm and a length of about 50-100μm.
[0066] Data and effects: The dispersibility and overlapping properties of fibrous gypsum in mortar are significantly improved, the crack resistance of mortar is enhanced by about 25%, and the toughness is improved by about 20%.
[0067] 6. Design of Nanorod Structure of Diatomite
[0068] Material processing: High-purity diatomaceous earth raw materials are selected and guided by hydrothermal method and template agent to form a nanorod structure. The diameter of the nanorod is about 50-100nm and the length is about 1-2μm.
[0069] Data and effects: The dispersion stability and long-range order of nanorod-structured diatomaceous earth in mortar are significantly improved, the mechanical properties of the mortar are enhanced by about 15%, and the durability is improved by about 10%.
[0070] Through the specific operations of the above embodiments, the structural design requirements of each component in the environmentally friendly mortar can be successfully achieved, thereby significantly improving the comprehensive performance and use effect of the mortar.
[0071] Embodiment 1
[0072] An environmentally friendly mortar comprises the following components in parts by weight: 450 parts of medium sand, 120 parts of silicate cement (Conch Cement), 30 parts of fly ash, 20 parts of lime (Wuxi Xinyue Environmental Protection Technology Co., Ltd.), 10 parts of gypsum (Guangzhou Jinsuihua Gypsum Products Co., Ltd.), 5 parts of diatomaceous earth (Lingshou County Jilu Mineral Products Processing Plant), 1 part of seaweed extract (Shandong Siyang Biotechnology), 4 parts of water-retaining thickener (wood fiber, Hebei Chaoyan New Material Technology Co., Ltd.), 1 part of retarder and early strength agent (sodium sulfate, Tianjin Shengxinyuan Weiye Trading Co., Ltd.), and 1 part of emulsifier (OP-10).
[0073] The embodiment also provides a method for preparing an environmentally friendly mortar, comprising the following steps:
[0074] S1: Using graded feeding technology, medium sand is added first, and the mixing time is 1 minute. After the medium sand is evenly mixed, silicate cement is added and stirred for 1 minute. Fly ash is added last and stirred for another 1 minute to ensure uniform mixing. Using atomized water spraying technology, the required amount of water is gradually added, and the stirring speed is increased at the same time. The initial speed is 50 rpm, and as water is added, it is gradually increased to 150 rpm to ensure that the water penetrates evenly into the mixture to form a mortar with uniform texture to obtain the basic mortar;
[0075] S2: Mix lime and gypsum, add water to form a slurry, and then slowly add it to the base mortar, stirring while adding, the addition rate is 5% of the volume of the base mortar per minute to give full play to its gelling effect, under the condition of continuous stirring, the stirring speed is increased to 60 rpm, the stirring time is 5 minutes, and diatomaceous earth is gradually added to improve the thermal insulation and adsorption of the mortar by using its porous structure. After the diatomaceous earth is added, continue to stir for 3 minutes to ensure uniform distribution;
[0076] S3: Use high-pressure spray equipment to evenly spray the seaweed extract aqueous solution on the mortar surface in a fine mist form. The spray pressure is controlled at 0.3MPa. At the same time, slow stirring is combined with the stirring speed controlled at 10 rpm to ensure that the seaweed extract can penetrate deeply into the mortar. Subsequently, the water-retaining thickener is added and stirred for 2 minutes to adjust the consistency of the mortar and improve its construction performance.
[0077] S4: Add retarder and early strength agent to adjust the setting time of mortar;
[0078] S5: Premix the emulsifier and water into a uniform emulsion, then add it to the mortar and stir it at high speed. The stirring speed is increased to 100 rpm and the stirring time is 10 minutes, so that the components in the mortar form a stable emulsified system, further improving the uniformity and stability of the mortar.
[0079] Embodiment 2
[0080] An environmentally friendly mortar comprises the following components in parts by weight: 470 parts of medium sand, 140 parts of silicate cement, 35 parts of fly ash, 22 parts of lime, 12 parts of gypsum, 8 parts of diatomaceous earth, 2 parts of seaweed extract, 5 parts of water-retaining thickener (wood fiber, Hebei Chaoyan New Material Technology Co., Ltd.), 3 parts of retarder and early strength agent (sodium sulfate, Tianjin Shengxinyuan Weiye Trading Co., Ltd.), and 2 parts of emulsifier (OP-10).
[0081] The embodiment also provides a method for preparing an environmentally friendly mortar, comprising the following steps:
[0082] S1: Using graded feeding technology, medium sand is added first, and the mixing time is 1 minute. After the medium sand is evenly mixed, silicate cement is added and stirred for 1 minute. Fly ash is added last and stirred for another 1 minute to ensure uniform mixing. Using atomized water spraying technology, the required amount of water is gradually added, and the stirring speed is increased at the same time. The initial speed is 60 rpm, and as water is added, it is gradually increased to 170 rpm to ensure that the water penetrates evenly into the mixture to form a mortar with uniform texture to obtain the basic mortar;
[0083] S2: Mix lime and gypsum, add water to form a slurry, and then slowly add it to the base mortar, stirring while adding, the addition rate is 6% of the volume of the base mortar per minute to give full play to its gelling effect, under the condition of continuous stirring, the stirring speed is increased to 65 rpm, the stirring time is 7 minutes, and diatomaceous earth is gradually added to improve the thermal insulation and adsorption of the mortar by using its porous structure. After the diatomaceous earth is added, continue to stir for 4 minutes to ensure uniform distribution;
[0084] S3: Use high-pressure spray equipment to evenly spray the seaweed extract aqueous solution on the mortar surface in a fine mist form. The spray pressure is controlled at 0.4MPa. At the same time, slow stirring is combined with the stirring speed controlled at 13 rpm to ensure that the seaweed extract can penetrate deeply into the mortar. Subsequently, the water-retaining thickener is added and stirred for 2 minutes to adjust the consistency of the mortar and improve its construction performance.
[0085] S4: Add retarder and early strength agent to adjust the setting time of mortar;
[0086] S5: Premix the emulsifier and water into a uniform emulsion, then add it to the mortar and stir it at high speed. The stirring speed is increased to 120 rpm and the stirring time is 14 minutes, so that the components in the mortar form a stable emulsified system, further improving the uniformity and stability of the mortar.
[0087] Embodiment 3
[0088] An environmentally friendly mortar comprises the following components in parts by weight: 490 parts of medium sand, 180 parts of silicate cement, 40 parts of fly ash, 24 parts of lime, 13 parts of gypsum, 11 parts of diatomaceous earth, 4 parts of seaweed extract, 6 parts of water-retaining thickener (wood fiber, Hebei Chaoyan New Material Technology Co., Ltd.), 6 parts of retarder and early strength agent (sodium sulfate, Tianjin Shengxinyuan Weiye Trading Co., Ltd.), and 3 parts of emulsifier (OP-10).
[0089] The embodiment also provides a method for preparing an environmentally friendly mortar, comprising the following steps:
[0090] S1: Using graded feeding technology, medium sand is added first, and the mixing time is 2 minutes. After the medium sand is evenly mixed, silicate cement is added and stirred for another 2 minutes. Fly ash is added last and stirred for another 2 minutes to ensure uniform mixing. Using atomized water spraying technology, the required amount of water is gradually added, and the stirring speed is increased at the same time. The initial speed is 80 rpm, and as water is added, it is gradually increased to 190 rpm to ensure that the water penetrates evenly into the mixture to form a mortar with uniform texture, thus obtaining the basic mortar;
[0091] S2: Mix lime and gypsum, add water to form a slurry, and then slowly add it to the base mortar, stirring while adding, the addition rate is 8% of the base mortar volume per minute to give full play to its gelling effect, under the condition of continuous stirring, the stirring speed is increased to 70 rpm, the stirring time is 8 minutes, and diatomaceous earth is gradually added to improve the thermal insulation and adsorption of the mortar by using its porous structure. After the diatomaceous earth is added, continue to stir for 4 minutes to ensure uniform distribution;
[0092] S3: Use high-pressure spray equipment to evenly spray the seaweed extract aqueous solution on the mortar surface in a fine mist form. The spray pressure is controlled at 0.4MPa. At the same time, slow stirring is combined with the stirring speed controlled at 17 rpm to ensure that the seaweed extract can penetrate deeply into the mortar. Subsequently, the water-retaining thickener is added and stirred for 3 minutes to adjust the consistency of the mortar and improve its construction performance.
[0093] S4: Add retarder and early strength agent to adjust the setting time of mortar;
[0094] S5: Premix the emulsifier and water into a uniform emulsion, then add it to the mortar and stir it at high speed. The stirring speed is increased to 130 rpm and the stirring time is 17 minutes, so that the components in the mortar form a stable emulsified system, further improving the uniformity and stability of the mortar.
[0095] Embodiment 4
[0096] An environmentally friendly mortar comprises the following components in parts by weight: 510 parts of medium sand, 200 parts of silicate cement, 50 parts of fly ash, 25 parts of lime, 15 parts of gypsum, 15 parts of diatomaceous earth, 5 parts of seaweed extract, 7 parts of water-retaining thickener (wood fiber, Hebei Chaoyan New Material Technology Co., Ltd.), 8 parts of retarder and early strength agent (sodium sulfate, Tianjin Shengxinyuan Weiye Trading Co., Ltd.), and 5 parts of emulsifier (OP-10).
[0097] The embodiment also provides a method for preparing an environmentally friendly mortar, comprising the following steps:
[0098] S1: Using graded feeding technology, medium sand is added first, and the mixing time is 2 minutes. After the medium sand is evenly mixed, silicate cement is added and stirred for another 2 minutes. Fly ash is added last and stirred for another 2 minutes to ensure uniform mixing. Using atomized water spraying technology, the required amount of water is gradually added, and the stirring speed is increased at the same time. The initial speed is 100 rpm, and as water is added, it is gradually increased to 200 rpm to ensure that the water penetrates evenly into the mixture to form a mortar with uniform texture, thus obtaining the basic mortar;
[0099] S2: Mix lime and gypsum, add water to form a slurry, and then slowly add it to the base mortar, stirring while adding, the addition rate is 10% of the volume of the base mortar per minute to give full play to its gelling effect, under the condition of continuous stirring, the stirring speed is increased to 80 rpm, the stirring time is 10 minutes, and diatomaceous earth is gradually added to improve the thermal insulation and adsorption of the mortar by using its porous structure. After the diatomaceous earth is added, continue to stir for 5 minutes to ensure uniform distribution;
[0100] S3: Use high-pressure spray equipment to evenly spray the seaweed extract aqueous solution on the mortar surface in a fine mist form. The spray pressure is controlled at 0.5MPa. At the same time, slow stirring is combined with the stirring speed controlled at 20 rpm to ensure that the seaweed extract can penetrate deeply into the mortar. Subsequently, the water-retaining thickener is added and continued to be stirred for 3 minutes to adjust the consistency of the mortar and improve its construction performance.
[0101] S4: Add retarder and early strength agent to adjust the setting time of mortar;
[0102] S5: Premix the emulsifier and water into a uniform emulsion, then add it to the mortar and stir it at high speed. The stirring speed is increased to 150 rpm and the stirring time is 20 minutes. This allows the components in the mortar to form a stable emulsified system, further improving the uniformity and stability of the mortar.
[0103] Comparative Example 1
[0104] An environmentally friendly mortar and a preparation method thereof are basically the same as those of the fourth embodiment, except that the process of adding diatomaceous earth in step S2 is omitted.
[0105] Comparative Example 2
[0106] An environmentally friendly mortar and a preparation method thereof are basically the same as those of the fourth embodiment, except that the process of adding seaweed extract in step S3 is omitted.
[0107] Comparative Example 3
[0108] An environmentally friendly mortar and a preparation method thereof are basically the same as those of the fourth embodiment, except that the process of adding a water-retaining thickener in step S3 is omitted.
[0109] Comparative Example 4
[0110] An environmentally friendly mortar and a preparation method thereof are basically the same as the fourth embodiment, except that the fly ash component is removed while the amounts of lime and gypsum are kept unchanged.
[0111] The mortars prepared in the above-mentioned Examples 1 to 4 and Comparative Examples 1 to 4 were tested:
[0112] Physical performance testing
[0113] Standard: GB / T 25181 "Premixed Mortar"
[0114] Test items: consistency, water retention, compressive strength, flexural strength, etc.
[0115] Testing method: Perform test operations and record data according to the methods specified in the standard.
[0116] Adhesion test
[0117] National standard: GB / T25181-2019 "Premixed Mortar" or other relevant mortar bonding performance standards.
[0118] Test method: The tensile bond strength test is usually used to evaluate the adhesion of mortar. After the specimens are prepared, they are cured under standard curing conditions to a specified age, and then the tensile bond strength of the specimens is measured using a tensile testing machine.
[0119] Thermal insulation test
[0120] National standard: GB / T20473-2021 "Building Thermal Insulation Mortar" or other relevant mortar thermal insulation performance standards.
[0121] Test method: The thermal insulation of mortar is evaluated by measuring its thermal conductivity. Prepare a specimen of a certain size and measure its thermal conductivity under standard conditions.
[0122] Adsorption test
[0123] National standard: Refer to JC / T1074-2008 "Purification Performance of Indoor Air Purification Functional Coating Materials" or other relevant mortar adsorption performance standards.
[0124] Test method: The adsorption of mortar on specific pollutants is evaluated by measuring the amount of adsorption of mortar on specific pollutants. Usually, the specimen is exposed to the pollutant environment under certain conditions, and then the amount of adsorption of pollutants on the specimen is measured.
[0125] The results are shown in Table 1:
[0126] Table 1
[0127]
[0128] From the above Table 1, we can clearly get the following:
[0129] From Example 1 to Example 4, the compressive strength gradually increases, and Example 4 shows the highest compressive strength of 35.6 MPa. This trend is consistent with the increase in the amount of each component, especially the increase in key cementitious materials such as silicate cement and fly ash, which helps to improve the compressive performance of the mortar.
[0130] The tensile bond strength also showed a trend of positive correlation with the example number, and the tensile bond strength of Example 4 was the highest, reaching 2.5 MPa. This shows that with the increase of the content of each component, especially the components that enhance the bonding property such as seaweed extract, the bonding force inside the mortar is effectively improved.
[0131] In terms of the adsorption capacity of formaldehyde, Example 4 also showed the best performance, with an adsorption amount of 0.51 mg / g. As a porous adsorption material, the increase in the content of diatomaceous earth in the mortar helps to improve the adsorption capacity of harmful substances such as formaldehyde.
[0132] The thermal conductivity of all examples remained at a low level of 0.70 W / (m·K), indicating that these mortar formulations performed well and were relatively stable in terms of thermal insulation performance. The porous structure of diatomite and the synergistic effect between the components help to reduce the thermal conductivity of the mortar and improve its thermal insulation performance.
[0133] In summary, from Example 1 to Example 4, the compressive strength, tensile bonding strength and formaldehyde adsorption capacity of the mortar all show excellent performance.
[0134] Reference Figure 1-2 , in Example 4 and Comparative Example where other conditions are the same:
[0135] 1. Compressive strength
[0136] Example 4: 35.6MPa
[0137] It shows high compressive strength, indicating that the mortar can withstand greater pressure without being easily damaged.
[0138] Comparative Example 1: 32.5MPa
[0139] Compared with Example 4, the compressive strength is reduced. Since the addition of diatomaceous earth is omitted, diatomaceous earth helps to enhance the structural stability of the mortar.
[0140] Comparative Example 2: 34.0MPa
[0141] The compressive strength was slightly lower than that of Example 4. Omitting the seaweed extract affected the strength development of the mortar to some extent.
[0142] Comparative Example 3: 31.3MPa
[0143] The compressive strength is significantly reduced. The lack of water-retaining thickener leads to uneven water distribution inside the mortar, which in turn affects its strength.
[0144] Comparative Example 4: 28.0MPa
[0145] The compressive strength is the lowest. Removing the fly ash component weakens the skeleton structure of the mortar, resulting in a decrease in its bearing capacity.
[0146] 2. Tensile bond strength
[0147] Example 4: 2.5MPa
[0148] It exhibits good tensile bond strength, indicating a strong bond between the mortar and the substrate.
[0149] Comparative Examples 1 to 4: All lower than Example 4
[0150] The decrease in tensile bond strength is related to the absence of components that form bond bridges in the mortar and enhance the bond properties.
[0151] 3. Formaldehyde adsorption
[0152] Example 4: 0.51 mg / g
[0153] It shows a high formaldehyde adsorption capacity, indicating that the mortar has good air purification function.
[0154] Comparative Example 1 and Comparative Example 4: The adsorption amount is significantly reduced
[0155] The absence of diatomaceous earth (Comparative Example 1) and the removal of fly ash (Comparative Example 4) both resulted in a significant decrease in formaldehyde adsorption, indicating that these components are crucial to the adsorption properties of the mortar.
[0156] Comparative Example 2 and Comparative Example 3: Very low adsorption
[0157] Omitting the seaweed extract (Comparative Example 2) or the water-retaining thickener (Comparative Example 3) almost caused the mortar to lose its ability to adsorb formaldehyde, indicating that these components play a key role in improving the adsorption performance of the mortar.
[0158] 4. Thermal conductivity
[0159] Example 4: 0.70W / (m·K)
[0160] The lower thermal conductivity means that the mortar has better thermal insulation properties.
[0161] Comparative Examples 1 to 4: All higher than Example 4
[0162] The increase in thermal conductivity indicates that the thermal insulation performance of the mortar has decreased. The absence of various components destroys the thermal resistance structure inside the mortar, making heat transfer easier.
[0163] In summary, diatomaceous earth, seaweed extract, water-retaining thickener and fly ash play important roles in mortar and jointly affect the physical properties and functional characteristics of mortar. The absence of these components will lead to different degrees of decline in mortar in terms of compressive strength, tensile bond strength, formaldehyde adsorption and thermal insulation performance. Therefore, when preparing environmentally friendly mortar, the synergistic effect of each component should be fully considered to ensure that the comprehensive performance of the mortar reaches the best state.
[0164] In the present invention, the seaweed extract can enhance the bonding and environmental protection of the mortar. The seaweed extract has biological activity, can improve the bonding of the mortar, and as a natural material, is conducive to environmental protection;
[0165] Diatomaceous earth improves the thermal insulation and adsorption of mortar. Diatomaceous earth has a porous structure, which can enhance the thermal insulation performance of mortar and absorb harmful substances in the air.
[0166] As an industrial waste, fly ash can replace part of cement and reduce resource consumption; lime and gypsum can react with the active ingredients in fly ash to generate hydration products with gelling properties. The combination of the three can not only realize the resource utilization of waste, but also improve the strength and durability of mortar.
[0167] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.
Claims
1. An environmentally friendly mortar, characterized in that: The invention comprises the following components in parts by weight: 450-510 parts of medium sand, 120-200 parts of silicate cement, 30-50 parts of fly ash, 20-25 parts of lime, 10-15 parts of gypsum, 5-15 parts of diatomaceous earth, 1-5 parts of seaweed extract, 4-7 parts of water-retaining thickener, 1-8 parts of retarder and early strength agent, and 1-5 parts of emulsifier.
2. The environmentally friendly mortar according to claim 1, characterized in that: The invention comprises the following components in parts by weight: 480 parts of medium sand, 150 parts of silicate cement, 35 parts of fly ash, 22 parts of lime, 13 parts of gypsum, 8 parts of diatomaceous earth, 3 parts of seaweed extract, 5 parts of water-retaining thickener, 3 parts of retarder and early strength agent, and 2 parts of emulsifier.
3. The environmentally friendly mortar according to claim 1, characterized in that: The particle size of the medium sand is in the range of 0.3-0.45 mm, the quartz content in the mineral composition of the medium sand is not less than 90%, and the sum of feldspar and other impurity minerals does not exceed 10%; The clinker mineral composition of the silicate cement is as follows: the content of tricalcium silicate is 50%-65%, the content of dicalcium silicate is 15%-30%, and the specific surface area of the silicate cement is 300-500m 2 / kg; The ignition loss of the fly ash is 1%-5%, the effective calcium oxide content in the lime is 85%-100%, and the CaSO4·2H2O content in the gypsum is 95%-99%; The pore volume of the diatomaceous earth is 0.6-1.2 cm 3 / g, pore size is 10-1000nm; The polysaccharide content in the seaweed extract is 60%-80%; The water-retaining thickener is one of wood fiber and cellulose ether, the slow-setting and early-strengthening agent is one of sodium sulfate and calcium sucrose, and the emulsifier is OP-10.
4. The environmentally friendly mortar according to claim 1, characterized in that: In the medium sand, the sand particles are distributed in a linear arrangement in the mortar, which helps to form an orderly skeleton structure; The silicate cement is modified; Compounding fly ash with other porous materials, including expanded perlite and ceramsite, to form a porous composite structure; In the lime, the lime particles have a hollow spherical structure and can form tiny bubbles in the mortar; In the gypsum, the gypsum particles have a mesoporous structure with a pore size of 2-50 nanometers.
5. The environmentally friendly mortar according to claim 1, characterized in that: The medium sand particles are designed with a multi-layer structure, each layer having different physical and chemical properties, including hardness and water absorption, so as to enhance the layering and versatility of the mortar, and / or the medium sand particles are designed with a hollow structure, which can reduce the weight of the mortar while maintaining its strength and stability; In the silicate cement, the silicate cement particles adopt a core-shell structure, the core is high-strength cement clinker, the shell is an auxiliary coating, the auxiliary coating includes waterproofing and corrosion resistance, and the silicate cement particles form a three-dimensional network structure in the mortar to increase the connection points and strength between the particles; In the fly ash, the fly ash particles are designed to be a honeycomb structure; In the lime, the lime particles are designed to be nano-sheet structures; In the gypsum, the gypsum particles adopt a fibrous structure; In the diatomaceous earth, the diatomaceous earth particles have a nanorod structure.
6. A method for preparing the environmentally friendly mortar according to any one of claims 1 to 5, characterized in that: The following steps are involved: S1: Mix medium sand, silicate cement and fly ash, stir them thoroughly in a dry state to ensure that the components are evenly distributed, add water and wet mix until the mixture presents a uniform mortar state to obtain a basic mortar; S2: Mix lime and gypsum, add water to form a slurry, and then slowly add it to the base mortar while stirring to give full play to its gelling effect. Under the condition of continuous stirring, gradually add diatomaceous earth to improve the thermal insulation and adsorption of the mortar by using its porous structure; S3: Spraying the seaweed extract in the form of an aqueous solution uniformly on the surface of the mortar obtained in S2, and then rapidly stirring it so that the seaweed extract can effectively penetrate into the mortar to enhance its adhesion and environmental protection. Subsequently, adding a water-retaining thickener to adjust the consistency of the mortar and improve its construction performance; S4: Add retarder and early strength agent to adjust the setting time of mortar; S5: Finally, add the emulsifier and stir at high speed to make the components in the mortar form a stable emulsified system, further improving the uniformity and stability of the mortar.
7. The method for preparing an environmentally friendly mortar according to claim 6, characterized in that: In S1, a graded feeding technology is adopted, wherein medium sand is first fed, then silicate cement is added, and finally fly ash is added. After each feeding, a short dry mixing is performed to ensure that each component is evenly distributed. Atomized water spraying technology is used to gradually add the required amount of water, while increasing the stirring speed to ensure that the water evenly penetrates into the mixture, forming a mortar with a uniform texture, thereby obtaining a basic mortar.
8. The method for preparing an environmentally friendly mortar according to claim 6, characterized in that: In S3, a high-pressure spray device is used to evenly spray the seaweed extract aqueous solution on the mortar surface in a fine mist, and slow stirring is combined to ensure that the seaweed extract can penetrate deeply into the mortar. Subsequently, a water-retaining thickener is added to adjust the consistency of the mortar and improve its construction performance.
9. The method for preparing an environmentally friendly mortar according to claim 6, characterized in that: In S5, the emulsifier and water are pre-mixed into a uniform emulsion, which is then added to the mortar and stirred at a high speed, so that the components in the mortar form a stable emulsified system, thereby further improving the uniformity and stability of the mortar.